Tanggung Jawab Notaris Terhadap Peralihan Protokol Notaris Yang Diserahkan Kepadanya - Nugroho, Rifqi Dwiakta; Silviana, Ana (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractA notary, a state-appointed public official sworn to execute legal duties, plays a crucial role in ensuring legal legitimacy within the field of law. The creation of an authentic notary deed involves the preservation of deed minutes as part of the notary protocol procedure, consisting of a deed copy and accompanying minutes. These minutes, integral to the notary protocol, are stored and maintained by the notary as they represent a significant state document. The storage of notary protocols is a distinct responsibility that mandates special care to prevent damage, thereby preserving the legal certainty of authentic deeds. This study endeavors to determine the extent of the notary recipient's responsibility for the entrusted protocol and their obligations under relevant laws and regulations. Employing a normative juridical approach, the research seeks to outline the notary's responsibilities concerning the notary protocol, both as a creator and as a recipient. The findings indicate that the notary bears responsibility for the notary protocol, irrespective of their role as the protocol recipient. The protocol recipient can be appointed directly by the concluding notary, the heirs of a deceased notary, or through direct appointment by the MPD, aligning with legal provisions.Keywords: notary; notary protocol; responsibilityAbstrakNotaris adalah merupakan pejabat publik yang ditunjuk dan disumpah oleh negara untuk mengemban jabatan sebagai pelaksana legalitas hukum di bidang hukum. Perihal pembuatan akta otentik notaris perlu menyimpan minuta akta sebagai prosedur protokol notaris, akta otentik terdiri atas Salinan akta dan minuta akta. Minuta akta disimpan dan di pelihara oleh notaris yang merupakan bagian dari protokol notaris yang harus dijaga karena merupakan dokumen negara. Penyimpanan protokol notaris adalah bentuk dari tanggung jawab notaris yang harus dilaksanakan notaris dengan penyimpanan yang khusus dan baik agar terhindar dari kerusakan dan tetap menjaga kepastian hukum dari akta otentik tersebut. Artikel ini bertujuan untuk mengetahui sejauh mana tanggung jawab notaris penerima protokol atas protokol yang diserahkan kepadanya dan berkewajiban secara hukum dan undang-undang yang berlaku. Metode penelitian menggunakan pendekatan yuridis normatif. Hasil penelitian diketahui bahwa tanggung jawab notaris terhadap protokol notaris dan sebagai penerima protokol notaris. Notaris penerima protokol dapat ditunjuk langsung oleh notaris yang telah mengakhiri masa jabatannya atau kepada ahli waris notaris yang telah meninggal dunia atau dapat ditunjuk langsung oleh MPD.Kata kunci: notaris; protokol notaris; tanggung jawab